Platelet-Released Growth Factors Modulate the Secretion of Cytokines in Synoviocytes under Inflammatory Joint Disease. (19th November 2017) - Tohidnezhad, Mersedeh; Bayer, Andreas; Rasuo, Biljana; Hock, Jennifer Vanessa Phi; Kweider, Nisreen; Fragoulis, Athanassios; Sönmez, Tolga Taha; Jahr, Holger; Pufe, Thomas; Lippross, Sebastian
Abstract : The etiology and pathogenesis of rheumatoid arthritis (RA) are marked by a complex interplay of various cell populations and is mediated by different signaling pathways. Traditionally, therapies have primarily focused on pain relief, reducing inflammation and the recovery of joint function. More recently, however, researchers have discussed the therapeutic efficacy of autologous platelet-rich plasma (PRP). The main objective of this work is to examine the influences of platelet-released growth factor (PRGF) on human synoviocytes under inflammatory conditions. Additionally, it is checked to which extend treatment with platelet concentrate influences the release of cytokines form synoviocytes. For this purpose, an in vitro RA model was created by stimulating the cells with the TNF- α . The release of cytokines was measured by ELISA. The cytokine gene expression was analyzed by real-time PCR. It has been observed that the stimulation concentration of 10 ng/ml TNF- α resulted in a significantly increased endogenous secretion and gene expression of IL-6 and TNF- α . The anti-inflammatory effect of PRGF could be confirmed through significant reduction of TNF- α and IL-1 β . An induced inflammatory condition seems to cause PRGF to inhibit the release of proinflammatory cytokines. Further study is required to understand the exact effect mechanism of PRGF on synoviocytes.